2005
DOI: 10.1144/gsl.sp.2005.249.01.11
|View full text |Cite
|
Sign up to set email alerts
|

The μ2M project on quantifying the effects of biofilm growth on hydraulic properties of natural porous media and on sorption equilibria: an overview

Abstract: The physical and chemical effects of bacterial biofilm formation upon hydraulic conductivity, mineral-solution interactions and the formation of biogenic mineral precipitates have been studied over a wide range of scales, from microscopic to macroscopic. Several novel pieces of equipment have been designed, constructed and commissioned in order to measure the physical effects of biofilms upon fluid flow through fractures and porous media, the overall effects of biofilm formation upon mineral surface reactivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
16
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 15 publications
4
16
0
1
Order By: Relevance
“…At a larger scale, this could have significant implications for geological waste repositories by 85 sorption of contaminants onto biofilm or uptake of contaminants onto mobile microbes. Similar observations were made by Brydie et al 6 who found that the hydraulic conductivity, expressed by a change in effluent discharge flow rate, had significantly dropped after inoculation of bacteria within quartz sand packed columns 90 due to biofilm formation. Furthermore, in the studies described here new mineral phases may precipitate within the rock pore spaces from porewater fluids and may contribute to this reduction in hydraulic conductivity.…”
Section: Discussionsupporting
confidence: 86%
“…At a larger scale, this could have significant implications for geological waste repositories by 85 sorption of contaminants onto biofilm or uptake of contaminants onto mobile microbes. Similar observations were made by Brydie et al 6 who found that the hydraulic conductivity, expressed by a change in effluent discharge flow rate, had significantly dropped after inoculation of bacteria within quartz sand packed columns 90 due to biofilm formation. Furthermore, in the studies described here new mineral phases may precipitate within the rock pore spaces from porewater fluids and may contribute to this reduction in hydraulic conductivity.…”
Section: Discussionsupporting
confidence: 86%
“…Where conditions are suitable there is potential for biofilaments to establish (in a matter of days) causing pore blockages resulting in a decrease in permeability of the porous media and a change in the local fluid flow patterns. Extensive formation of biofilm reduces pore space, which can lead to eventual blocking of the pore system (Taylor and Jaffé 1990a;Taylor et al 1990) referred to as 'bioclogging' (Brydie et al 2005). Brydie et al (2005) observed a 70 % reduction in the permeability of sand due to bioclogging.…”
Section: Microbial Transport Studies Associated With the äSpö Hard Romentioning
confidence: 99%
“…Extensive formation of biofilm reduces pore space, which can lead to eventual blocking of the pore system (Taylor and Jaffé 1990a;Taylor et al 1990) referred to as 'bioclogging' (Brydie et al 2005). Brydie et al (2005) observed a 70 % reduction in the permeability of sand due to bioclogging. Even greater permeability reductions (three orders of magnitude) were observed in earlier studies by Taylor and Jaffé (1990a).…”
Section: Microbial Transport Studies Associated With the äSpö Hard Romentioning
confidence: 99%
See 2 more Smart Citations